Interaction Mechanisms Between the NOX4/ROS and RhoA/ROCK1 Signaling Pathways as New Anti- fibrosis Targets of Ursolic Acid in Hepatic Stellate Cells - Huang, Chenkai; Gan, Dakai; Luo, Fangyun; Wan, Sizhe; Chen, Jiang; Wang, Anjiang; Li, Bimin; Zhu, Xuan (Frontiers in Pharmacology, 2019)
Background: Studies have shown that both NOX4 and RhoA play an important role in fibrosis and that they regulate each other. In lung fibrosis, NOX4/ROS is an upstream molecule of the RhoA/ROCK1 signalling pathway, and the two molecules are opposite in renal fibrosis. At present, no reports have indicated whether the above similar or other regulatory mechanisms exist in liver fibrosis. Objectives: To investigate the effects of NOX4/ROS and RhoA/ROCK1 signalling pathways on the behaviour of HSC-T6 cells and their interaction mechanisms, as well as the effect of UA on the two signalling pathways to elucidate the role of UA in the reduction of hepatic fibrosis and potential mechanisms of HSC-T6 cell proliferation, migration, and activation. Method: Stable cell lines were constructed using lentiviral transfection technique. Cell proliferation, apoptosis, migration, and invasion were examined using MTS, TUNEL, cell scratch, and Transwell invasion assays, respectively. The DCFH-DA method was used to examine ROS levels in each group. RT-qPCR and Western blotting techniques were utilized to detect mRNA and protein expression levels in each group. CoIP and the Biacore protein interaction analysis systems were used to evaluate protein-protein interactions. Results: NOX4/ROS and RhoA/ROCK1 signalling pathways promoted the proliferation, migration and activation of HSC-T6 cells. UA inhibited cell proliferation, migration and activation by inhibiting the activation of the two signalling pathways, but the mechanism of apoptosis was independent of these two pathways. The NOX4/ROS pathway in HSC-T6 cells was upstream of the RhoA/ROCK1 pathway and positively regulated the RhoA/ROCK1 pathway. No direct interaction between NOX4 and RhoA proteins was detected. Conclusions: The NOX4/ROS and RhoA/ROCK1 signalling pathways are two important signalling pathways in a series of behavioural processes of HSC-T6 cells, and NOX4/ROS regulates RhoA/ROCK1 through an indirect pathway to regulate the activation of HSC-T6 cells. In addition, NOX4/ROS, RhoA/ROCK1 is a new target for UA anti-fibrosis treatment.